2006
DOI: 10.1177/0305735606067158
|View full text |Cite
|
Sign up to set email alerts
|

Musical influences in advertising: how music modifies first impressions of product endorsers and brands

Abstract: The ability of music to create differentiating effects on subjects’ impressions of product endorsers and brands of an advertisement were examined based on the theory of ‘musical fit’. Subjects ( N = 132) listened to one of three versions of a radio commercial in which the music varied in each version. The music selections differed in style, tempo, rhythm, etc., but matched product and message of the commercial in terms of ‘musical fit’. After listening to the commercial, subjects rated the endorser's personali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
49
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(58 citation statements)
references
References 28 publications
5
49
0
Order By: Relevance
“…music that is perceived as pleasant can create a pleasing feeling toward the brand), others have failed to obtain this effect (e.g. Gorn, 1982;Zander, 2006). Research on music-message fit (Alpert and Alpert, 1991;MacInnis and Park, 1991) suggests that creating new associations between music and brand should be easiest with a strong fit of the music to the message and brand image.…”
Section: Cognitive Componentsmentioning
confidence: 99%
“…music that is perceived as pleasant can create a pleasing feeling toward the brand), others have failed to obtain this effect (e.g. Gorn, 1982;Zander, 2006). Research on music-message fit (Alpert and Alpert, 1991;MacInnis and Park, 1991) suggests that creating new associations between music and brand should be easiest with a strong fit of the music to the message and brand image.…”
Section: Cognitive Componentsmentioning
confidence: 99%
“…In regard to musical styles or genres researchers have not found any factors that decrease or increase the attitude towards the advertisement or recall of the product or brand. But the genre significantly influences a recipient's impressions of the promoted product (Zander et al, 2010;Zander, 2006) and the perceived mood (for example happy versus sad) of the applied music has an impact on (Alpert et al, 2005). The effects of musical characteristics (for example, tempo, loudness, or mode) were examined in various studies but results were often contradictory (for an overview of the results see Schramm & Spangardt, 2016).…”
Section: Advertising With Musicmentioning
confidence: 99%
“…For example, it has been demonstrated that loud or fast music leads people to move and also to eat and drink more quickly (Smith and Curnow, 1966;Milliman, 1982;Roballey et al, 1985;Milliman, 1986;McElrea and Standing, 1992), whereas slow music in a minor key leads people to spend more time and, consequently, increases consumption ; see also Milliman, 1986). Furthermore, it has been suggested that music modifies people's first impressions of products (Zander, 2006), and influences their choices when deciding between two competing foods (Yeoh and North, 2010).…”
Section: Influence Of Musicmentioning
confidence: 99%